Phytoplankton Composition of Santubong Estuary - Nik Zulaikha, Binti Nik Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A study of phytoplankton composition in Santubong estuary was carried out to determine the cell density and abundance of phytoplankton species and relationship with environmental factors. A total of ten sampling trips were undertaken at the estuary from October 2013 to February 2014. The phytoplankton composition recorded in the estuary was dominated by diatoms group. The highest cell density recorded was 7.2 × 104 cells L-1 and the lowest cell density was 3.6 × 104 cells L-1 . The predominant groups of phytoplankton observed in this study were Coscinodiscus sp., Cyclotella sp. and Nitzschia sp. Moreover, the phytoplankton composition in the estuary was affected by several environmental factors, i.e. temperature, salinity, water transparency and pH as well as macronutrients. Each factor showed different degree of correlation with the phytoplankton community structure.